Cover Image, Volume 114, Number 4, April 2017. Issue 4 (21st February 2017) - Liu, Dong‐Feng; Min, Di; Cheng, Lei; Zhang, Feng; Li, Dao‐Bo; Xiao, Xiang; Sheng, Guo‐Ping; Yu, Han‐Qing
Abstract : Cover Legend The cover image, by Dong‐Feng Liu et al., is based on the Article Anaerobic reduction of 2, 6‐dinitrotoluene by Shewanella oneidensis MR‐1: Roles of Mtr respiratory pathway and NfnB, DOI:10.1002/bit.26212 .